Improving energy efficiency through technology trends, investment behaviour and policy design - Florax, R. J. G. M. 1956-; Groot, Henri L. F. de; Mulder, Peter 1974- (Cheltenham, UK Edward Elgar Publishing, 2011)
This innovative book explores the adoption of energy-saving technologies and their impact on energy efficiency improvements. It contains a mix of theoretical and empirical contributions, and combines and compares economic and physical indicators to monitor and analyse trends in energy efficiency. The authors pay considerable attention to empirical research on the determinants of energy-saving investment including uncertainty, energy-price volatility and subsidies. They also discuss the role of energy modelling in policy design and the potential effect of energy policies on technology diffusion -- Source other than Library of Congress.
Energy efficiency and technological change -- pt. I. Trends in energy efficiency -- A spatial perspective on global energy productivity trends -- Energy-productivity performance across 14 OECD countries : the role of energy-extensive sectors -- Using physical indicators to monitor energy efficiency in energy-extensive sectors -- Monitoring energy use and energy efficiency in the Dutch service sector -- pt. II. Technology and investment behaviour -- Adoption criteria, diffusion and firm size : the role of learning in reconciling theories of endogenous technical change with empirical evidence -- A meta-regression analysis of the investment-uncertainty relationship -- The effects of uncertainty on investments : analysing the environmental impact of energy market liberalization -- pt. III. Energy policy design -- Energy investment behaviour : firm heterogeneity and subsidy design -- Effectiveness of energy policies in the service sector -- Energy model and policy advice : the effect of model choice -- Conclusions and future research.
Includes bibliographical references and index.
Keywords: Energy conservation -- Equipment and supplies; Energy consumption -- Technological innovations